1989
DOI: 10.1007/bf00441948
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogenic drug interactions at human brain 5-HT2 receptors: implications for treating LSD-induced hallucinogenesis

Abstract: It has been shown that the hallucinogenic potencies of LSD, the phenylisopropylamines, such as DOB (4-bromo-2,5-dimethoxyphenylisopropylamine) and DOI (4-iodo-2,5-dimethoxyphenylisopropylamine), and the indolealkylamines, such as DMT (dimethyltryptamine) and 5-OMe-DMT (5-methoxy-dimethyltryptamine), strongly correlate with their in vitro 5-HT2 receptor binding affinities in rat cortical homogenates. In order to ascertain if this correlation applies to human 5-HT2 receptors as well, we examined the affinities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 16 publications
2
86
0
Order By: Relevance
“…The tryptamine with the lowest 5-HT 2A receptor affinity, DiPT, is psychoactive at 20-100 mg (Shulgin and Carter, 1980;Tittarelli et al, 2015). For the seven tryptamines that were evaluated in the present study, we found a significant correlation between 5-HT 2A receptor binding affinity and the estimated average doses at which the tryptamines are psychoactive in humans (Tittarelli et al, 2015) as previously shown for other hallucinogens (Sadzot et al, 1989;Titeler et al, 1988). In contrast, 5-HT 2A receptor activation potency did not correlate with the human doses.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The tryptamine with the lowest 5-HT 2A receptor affinity, DiPT, is psychoactive at 20-100 mg (Shulgin and Carter, 1980;Tittarelli et al, 2015). For the seven tryptamines that were evaluated in the present study, we found a significant correlation between 5-HT 2A receptor binding affinity and the estimated average doses at which the tryptamines are psychoactive in humans (Tittarelli et al, 2015) as previously shown for other hallucinogens (Sadzot et al, 1989;Titeler et al, 1988). In contrast, 5-HT 2A receptor activation potency did not correlate with the human doses.…”
Section: Discussionsupporting
confidence: 81%
“…The affinity of hallucinogens at the 5-HT 2A receptor but not at the 5-HT 1A receptor has been shown to correlate with psychoactive potency in humans (Sadzot et al, 1989;Titeler et al, 1988). The tryptamines that were tested in the present study all exhibited significantly lower affinity to the 5-HT 2A receptor compared with LSD.…”
Section: Discussionmentioning
confidence: 53%
“…The 5-HT 2A receptor agonists such as mCPP have been shown to decrease learning and memory in rats (Meneses, 1999). The same mechanism might be responsible for the decrement in learning and delayed recall following MDMA administration, as it has been previously demonstrated that MDMA possesses a moderate affinity for activating the 5-HT 2A receptor (Sadzot et al, 1989).…”
Section: Introductionmentioning
confidence: 61%
“…The elevations also may be related to the ability of toxic doses of lithium to cause auditory or visual hallucinations (Hambrecht and Kaumeier, 1993) or photophobia (Pridmore et al, 1996). On the other hand, lithium's blocking of the k* increments in response to DOI, a recognized hallucinogen (Sadzot et al, 1989), in visual and auditory areas and the substantia nigra and locus coeruleus, may relate to its ability to reduce hallucinations in bipolar disorder (Goodnick and Meltzer, 1984;Potash et al, 2001;Rosenthal et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…DOI, a hallucinogen (Sadzot et al, 1989), has a high and equal affinity for 5-HT 2A and 5-HT 2C receptors (http://kidb.cwru.edu/pdsp/php, 2003), which can be coupled to PLA 2 (Bayon et al, 1997;Qu et al, 2003). We chose a DOI dose of 1 mg/kg i.p.…”
Section: Introductionmentioning
confidence: 99%